2015
DOI: 10.5339/gcsp.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

Serum and tissue biomarkers in aortic stenosis

Abstract: Background: Calcific aortic valve stenosis (CAVS) is seen in a large proportion of individuals over 60 years. It is an active process, influenced by lipid accumulation, mechanical stress, inflammation, and abnormal extracellular matrix turnover. Various biomarkers (BMs) are studied, as regards mechanisms, diagnosis and prognosis. Methods: In the calcified valves calcium deposition, elastin fragmentation and disorganization of cellular matrix were assessed, together with expression of OPN, OPG, osteocalcin (OCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 62 publications
1
30
0
2
Order By: Relevance
“…[36][37][38] Inflammatory cells such as macrophages and lymphocytes that have been recruited to the fibrosa release inflammatory cytokines and matrix metalloproteinases, leading to degradation of cusp collagen and proteoglycans. [39][40][41][42] These biological events lead to osteoblastic transition of valve interstitial cells and active cusp calcification.- 37,38 As a result, with time the calcified valve becomes increasingly rigid and stenotic.…”
Section: Pathophysiology In Asmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38] Inflammatory cells such as macrophages and lymphocytes that have been recruited to the fibrosa release inflammatory cytokines and matrix metalloproteinases, leading to degradation of cusp collagen and proteoglycans. [39][40][41][42] These biological events lead to osteoblastic transition of valve interstitial cells and active cusp calcification.- 37,38 As a result, with time the calcified valve becomes increasingly rigid and stenotic.…”
Section: Pathophysiology In Asmentioning
confidence: 99%
“…87 MDA levels appear to be increased in patients with AS and were shown to be predictive of worse outcomes, including increased risk of dying after TAVR. 39,42 In these studies, MDA levels provided incremental value over the EuroSCORE for risk prediction.…”
Section: Markers Of Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Данный биомаркер играет важную роль в ремоделировании костной ткани, а также принимает участие в эктопи-ческой кальцификации, активируя дифференцировку миофибробластов в остеобласты [23,24]. Ранее Yu PJ, [23,25]. Аналогичные результаты проведенного нами иссле-дования также подтверждают возможное участие остеопонтина в развитии АС, вероятно, за счет акти-вации процессов воспаления.…”
Section: материал и методыunclassified
“…First of all, GLS was found to be related to biomarkers of myocardial fibrosis such as those expressing calcification, collagen formation, or breakdown and inflammation [42, 43]. Several studies have also reported significant associations between LV systolic function and both FMF and DMF at CMR or myocardial histology [3, 14, 15, 18, 19, 24, 29, 44-46] (Table 2).…”
Section: Relationship Between Myocardial Fibrosis and LV Systolic Funmentioning
confidence: 99%